Design and implementation of a resource operation and maintenance system based on container arrangement technology - Xun ZHANG; Chengyu ZHANG; Jinwu WEI (Dianxin kexue)
Kubernetes container layout tools,Docker operation technology and Mesos framework choreography technology selection were used to solve China Unicom’s existing problems of business application container’s unbalance of resource scheduling.The problem of existing physical cluster elastic scalability capacity was solved.Through cluster and the technique of Mesos,the original big data deploy faster and the scalability problems were solved.Finally,container operation and management system was realized.